Peran Organizational Learning Capability dan Service Innovation Dalam Memediasi Entrepreneurial Orientation dan Organizational Performance pada UMKM F&B Di Pasar Lama Tangerang - Simon, Matthew; Hosen, Chandra (Universitas Bunda Mulia, 2025)
SMEs play a crucial role in Indonesia's economy, particularly in the rapidly growing F&B sector. This study analyzes the impact of Entrepreneurial Orientation and Organizational Learning Capability on Organizational Performance, with Service Innovation as a mediating variable. Data from 69 respondents were analyzed using Partial Least Square (PLS) with SmartPLS version 4.1.0.8. The results indicate that Service Innovation and Organizational Learning Capability do not mediate the relationship between Entrepreneurial Orientation and Organizational Performance. However, Organizational Learning Capability fully mediates the relationship between Entrepreneurial Orientation and Service Innovation. These findings highlight the critical role of organizational learning in driving service innovation to enhance the competitiveness of F&B SMEs. The novelty of this study lies in its simultaneous analysis of the role of organizational learning capability and service innovation within the SME ecosystem, providing valuable insights for business owners in designing innovation-based performance improvement strategies.